The Orang Asli in Malaysia: the legal protection of their rights to land / Nur Izzaina Yuhana … [et al.] - Yuhana, Nur Izzaina; Hairan, Norhaslinda; Faizal, Farida Cheryl; Abu Hassan, Nurrul Dayana (Faculty of Law, 2006)
This project paper is a study of the adequacy of legal protection of rights to land of Orang Asli in Peninsular Malaysia. The law that governs Orang Asli is the Aboriginal Peoples Act 1954 (Revised-1974) which carries the purpose of protecting the welfare and socio economic of the Orang Asli. However, this law does not provide assistance regarding the matter of Orang Asli's land tenure. Furthermore, Orang Asli's rights to land are deprived by encroachments by various parties. Therefore, this project paper is to propose relevant recommendations to overcome this matter.